In Vitro Evaluation of the Probiotic Properties and Whole Genome Sequencing of Lacticaseibacillus rhamnosus J3205 Isolated from Home-Made Fermented Sauce - Yiming Chen; Lingchao Ma; Weiye Chen; Yiwen Chen; Zile Cheng; Yongzhang Zhu; Min Li; Yan Zhang; Xiaokui Guo; Chang Liu (Microorganisms)
Lacticaseibacillus rhamnosus J3205 was isolated from traditional fermented sauces and demonstrated potential probiotic properties. The strain exhibited high tolerance to simulated saliva (93.24% survival) and gastrointestinal conditions (69.95% gastric and 50.44% intestinal survival), along with strong adhesion capacity (58.25%) to intestinal epithelial cells. Safety assessments confirmed the absence of virulence and antibiotic resistance genes. Genomic analysis revealed stress-response genes and 34 insertion sequence (IS) elements, while proteomic profiling identified Pgk as a key enzyme in lactic acid production and SecY in oxidative stress resistance. Functionally, J3205 significantly reduces pro-inflammatory cytokines (TNF-α, IL-6, IL-1β) and enhances antioxidant markers (SOD, GSH) in vitro. These results position L. rhamnosus J3205 as a promising candidate for gut-health foods, anti-inflammatory nutraceuticals, and oxidative-stress therapeutics, warranting further in vivo validation.